2017
DOI: 10.5539/ijps.v9n3p51
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction Evaluation of the Effectiveness of the Two Models of Specialty-Oriented Career Planning Course

Abstract: This research is a two-semester experimental program that uses Freshman's "Finance Career Planning" of the undergraduate program of the finance department of the National Taipei University of Business (NTUB) as the experimental curriculum. This research explores and analyzes two models of "Specialty-oriented career planning course" to see if there is a difference in students' course satisfaction. The features of the second model include specialty-oriented lectures by finance alumni and assignments requiring th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…The similar finding as Peng, Y. H. Lin, and C. J. Lin's (2017) that compared with the traditional one-way lecture model, the most effective learners' satisfaction model is the model of including specialty-oriented lectures by finance alumni and assignments requiring the interviewing of upperclassmen, in addition to studying career counseling theory and specialty-topic content sharing. Taber and Blankemeyer (2015) indicated that future work self-predicted career planning and that career concern had an additive effect.…”
Section: Audio-visual Teaching Methods Turn a Career Planning Course supporting
confidence: 65%
See 1 more Smart Citation
“…The similar finding as Peng, Y. H. Lin, and C. J. Lin's (2017) that compared with the traditional one-way lecture model, the most effective learners' satisfaction model is the model of including specialty-oriented lectures by finance alumni and assignments requiring the interviewing of upperclassmen, in addition to studying career counseling theory and specialty-topic content sharing. Taber and Blankemeyer (2015) indicated that future work self-predicted career planning and that career concern had an additive effect.…”
Section: Audio-visual Teaching Methods Turn a Career Planning Course supporting
confidence: 65%
“…When entering their future workplace, they will continue learning for a lifetime, while improving job satisfaction, and treating their chosen professionals as "business careers" and "life careers". We hope that every college department will actively promote the "specialty-oriented career planning courses" to improve college students' "specialty employment rate", thereby enhancing the national competency in professional talent development (Lin & Peng, 2015;Peng, Y. Lin, & C. Lin, 2017).…”
Section: Program Focus and Strategy Scopementioning
confidence: 99%
“…In particular, the fit of an individual's "majored subject and professional interest" affects learning motivation and academic performance. Specialty-Oriented Career Counseling courses in higher education can help promote the focus of all college departments on their assisting college students' self-exploration and profession cultivation within their specialty-oriented career development (Peng, Lin & Lin, 2017; Peng, 2015 a ). Petty (2014) emphasizes that all departments in colleges and universities should provide a series of career counseling programs to help students face the challenges of their professional learning careers.…”
Section: Specialty Major and Specialty-oriented Career Counselingmentioning
confidence: 99%
“…Career planning courses should be scheduled as an elective for all departments during the freshman year in colleges (Herr, 2001;Peng & Herr, 1999). The emphasis is on the significance of professional orientation and career planning, in order to enhance the employability, competitiveness and employment rates of college students (Peng, 2016;Peng, Lin, & Lin, 2017). The specialty-oriented career counseling courses should be well-designed and catering to different departments.…”
Section: Career Decision-making and Career-planning Coursesmentioning
confidence: 99%